Bloodstream Infections caused by Klebsiella pneumoniae and Serratia marcescens isolates co-harboring NDM-1 and KPC-2 - Taniela Bes; Debora Nagano; Roberta Martins; Ana Paula Marchi; Lauro Perdigão-Neto; Hermes Higashino; Gladys Prado; Thais Guimaraes; Anna S. Levin; Silvia Costa (BMC, 2021)
Abstract Carbapenem-resistant Enterobacteriaceae are a worldwide health problem and isolates carrying both bla KPC-2 and bla NDM-1 are unusual. Here we describe the microbiological and clinical characteristics of five cases of bloodstream infections (BSI) caused by carbapenem-resistant Klebsiella pneumoniae and Serratia marcescens having both bla KPC-2 and bla NDM-1. Of the five blood samples, three are from hematopoietic stem cell transplantation patients, one from a renal transplant patient, and one from a surgical patient. All patients lived in low-income neighbourhoods and had no travel history. Despite antibiotic treatment, four out of five patients died. The phenotypic susceptibility assays showed that meropenem with the addition of either EDTA, phenylboronic acid (PBA), or both, increased the zone of inhibition in comparison to meropenem alone. Molecular tests showed the presence of bla KPC-2 and bla NDM-1 genes. K. pneumoniae isolates were assigned to ST258 or ST340 by whole genome sequencing. This case-series showed a high mortality among patients with BSI caused by Enterobacteriae harbouring both carbapenemases. The detection of carbapenemase-producing isolates carrying both bla KPC-2 and bla NDM-1 remains a challenge when using only phenotypic assays. Microbiology laboratories must be alert for K. pneumoniae isolates producing both KPC-2 and NDM-1.